Assessing the role of entrepreneurship in empowering women in Tanzania: A case of rosella wine entrepreneurs in Bukoba municipality - Rugamara, Bernard (Mzumbe University, 2024)
A dissertation submitted to Mzumbe university as a partial of the requirements for the ward of the Master’s degree in Business Administration-Corporate Management of Mzumbe University